Time to re-think our strategy with musculoskeletal disorders and workstation ergonomics - Vanessa S. Redivo; Benita Olivier (AOSIS, 2021)
Background: The dramatic increase in visual display units (VDU) in the workplace over a 20-year period is linked to the increased prevalence of musculoskeletal disorders (MSDs). Objectives: The objective of our study was to compare ergonomic risk factors and work-related psychosocial factors in VDU users with and without MSD. Methods: Participants, with and without MSD, working with VDU for more than 4 h a day completed the Nordic Musculoskeletal Questionnaire and the Effort-Reward Imbalance Model and Over-commitment Questionnaire. The workstation of each participant was assessed for ergonomic risk factors using the Rapid Office Strain Assessment (ROSA). Results: Sixty-eight VDU users with and 68 without MSDs participated. The workstation ergonomic risk factors as measured with the ROSA were similar for the two groups: 4.5 ± 1.0 for the MSD group and 4.3 ± 0.8 for the reference group (p = 0.10). The work-related psychosocial factors, namely over-commitment, were higher in the MSD group (14.9 ± 3.1) than in the reference group (13.8 ± 3.4; p = 0.041). Conclusions: As over-commitment is an indication of intrinsic factors and personal characteristics, the significant difference between the MSD group's over-commitment score and that of the reference group suggests that interventions to empower individuals are needed. Clinical implications: Physiotherapists should only adjust ergonomic workstation risk factors when established as contributory to MSD, and should be cognisant of work-related or individual psychosocial factors that may impact the patient with MSD. The use of ergonomic advice to patients with MSD should be performed with caution, taking all the work place risk factors for MSD into account.